Determination of Selected Nursing Transcripts for E-health/E-nursing Education - Rasmeh Al-Huneiti; Mohammed Al Masarweh; Ziad Hunaiti; Ebrahim Mansour; Wamadeva Balachanrdan (Issues and Development in Health Research Vol. 6, 2021)
This paper reports on research concerning the establishment of an E-learning framework to impart E-health education to nurses in developing countries. Nursing and midwifery academic transcripts from several schools of nursing in different developing countries for nurse graduated in the years 2005-2009 were analyzed to evaluate their contents regarding Information Communication Technology (ICT) and E-health/E-nursing courses. Content analysis mechanism for 24 transcripts from eight developing countries were analyzed, this analysis revealed that there was no evidence of the introduction of the concept of E-health/E-nursing as such in any of the transcripts studied; Most of the programs ( 75%) were four years long, the vast majority (87%) of programmes had some kind of ICT- or computer-related modules, mostly concerning basic computer skills and IT fundamentals. The study finding justify the need for integration of E-health/E-nursing learning module in nursing curricula for national nursing institutions, and E-health literacy should be a prerequisite for the registration of general scope nurses/medical students